1999
DOI: 10.1046/j.1365-2044.1999.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative silent myocardial ischaemia in patients undergoing lower limb joint replacement surgery: an indicator of postoperative morbidity or mortality?

Abstract: SummaryOne hundred and twenty-seven patients undergoing major lower limb joint replacement surgery were studied to determine the incidence of silent myocardial ischaemia and to ascertain any link between pre-operative cardiac risk factors, silent myocardial ischaemia and postoperative morbidity. Patients underwent ambulatory ECG monitoring for 4 days (on the pre-operative night and for 3 days postoperatively). Postoperative cardiorespiratory symptomatology and morbidity was assessed by questionnaire at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The myocardial infarction rate in our study was 0.35%, with mortality reported following 273 (14.3%) of 1,906 procedures. This did not, however, take into consideration the possibility of silent myocardial infarction 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The myocardial infarction rate in our study was 0.35%, with mortality reported following 273 (14.3%) of 1,906 procedures. This did not, however, take into consideration the possibility of silent myocardial infarction 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of myocardial ischaemia, which may be considered a surrogate for myocardial events, is relatively much higher and can be detected and quantified by Holter continuous ambulatory electrocardiogram (ECG) monitoring [12–14]. Previous studies have reported that silent myocardial ischaemia (SMI) can be found in up to 30% of patients during the perioperative period following non‐cardiac surgery [15–20]. Both increased incidence and duration of perioperative SMI are associated with adverse outcomes [21–23].…”
Section: Introductionmentioning
confidence: 99%
“…Methods available for the detection of damage include ambulatory electrocardiograph (ECG) recording, cardiac scanning and the measurement of blood concentrations of cardiac‐specific proteins. We previously reported the poor specificity of ambulatory ECG as an indicator of postoperative cardiovascular complications in noncardiac surgical patients [1–3].…”
mentioning
confidence: 99%